Determinants of an integrated cervical cancer screening services in primary healthcare: sharing lessons from Kisumu, Kenya - Eyo Akpan; Nicholas Abinya; Everlyne Odhiambo; Ernest Ekpo (AOSIS, 2023)
Background: The successful integration of cervical cancer screening service (CCASS) into primary healthcare's routine services depends on locality-specific and context-based service determinants. Objective: This paper aims to identify the abovementioned determinants and discusses how health administrators can manage their influence on CCASS delivery at the primary healthcare level. Methods: We conducted in-depth face-to-face interviews using a structured questionnaire with CCASS nurse providers and managers in four randomly selected primary health facilities. Information on the method(s) of screening utilised, the challenges faced, and the changes observed in CCASS provision were collected. Service managers were asked how they managed unplanned CCASS disruption, factors influencing CCASS replication, and aftercare support to cancer-affected women. Nurse providers were interviewed on the management of CCASS awareness and critical changes required to sustain CCASS service effectiveness. We used a constant interactive and inductive approach for data analysis. Results: Nine thematic categories of CCASS determinants were identified: 'cultural', 'socioeconomic', 'individual', 'health system', 'evidence-based operations', 'outcome-based resourcing', 'workflow improvement and standardisation', 'inclusive partner's management', 'utilisation'. These determinants were grouped into three domains: 'conceptual', 'outcomes', and 'growth' domains, to correspond to clusters of determinants that are likely to influence the CCASS lifecycle in its formative, continuous delivery or productivity, and reproductive phases. Conclusions: The findings show that sustaining an efficient integrated CCASS delivery at the PHC level requires phase-appropriate continuous adaptive improvements of service determinants within that locality.